Magnetite–Corrole Hybrid Nanoparticles - Rute A. Pereira (Magnetochemistry, 2018)
This study describes the first example of a hybrid material comprising corrole- and silica-coated magnetite nanoparticles. Firstly, cuboid and spheroid magnetite nanoparticles were prepared using a simple hydrothermal route, followed by a silica coating. The hybrid nanoparticles were obtained by promoting a covalent link between a gallium (III)(pyridine) complex of 5,10,15-tris(pentafluorophenyl)corrole (GaPFC) and the surface of magnetite–silica core/shell nanoparticles (Fe3O4@SiO2), shaped both as cuboids and spheroids. The hybrids were characterized using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), ultraviolet-visible spectrophotometry (UV-Vis) and transmission electron microscopy (TEM). Preliminary studies on the capacity of singlet oxygen generation of the hybrid nanoparticles showed that these have lower efficiency values when compared to the pure corrole compound.